The thermal decomposition of silver oxide - Herley, Patrick James (Rhodes University, Faculty of Science, Department of Chemistry, 1960)
[From Introduction]. The thermal decomposition of solids is characterized by the formation and growth of nuclei at sites on the surface of the solid or within the crystal lattice. Such nuclear formation is favoured by disorganisation of the crystal either by mechanical damage, or by the presence of impurities. Disorganisation results in positions which have a high thermodynamic instability. The nuclei are likely to be formed initially at the corners and the edges of the crystal since these are more prone to damage. Careful handling and storage in vacuo often leads to a large reduction in their number, while deliberate scratching of the surface facilitates their production. The number of potential sites for nuclear formation is also increased by pre-irradiation with ultra-violet light, though there are indications that a different type of nucleus may be produced. Nucleation can be facilitated by pre-irradiation with electrons, neutrons, X-rays, gamma-rays and atomic particles. The nature of the nuclei is not always clearly defined, but it is generally accepted that they are composed of solid reaction products e.g. in the decomposition of barium azide and silver oxalate, nuclei of metallic barium and silver, respectively, are formed.
Keywords: Silver oxide -- Thermal properties; Decomposition (Chemistry)